An Overview of The Public Relations Function, second Edition - Bowen, Shannon A. (Public relations collection., 2019)
This second edition of An overview of the public relations function examines current thought to help busy managers and students master the most important concepts of management in communication quickly, accessibly, and with an eye to helping an organization achieve excellence through cutting-edge, research-based strategic public relations management.